2010
DOI: 10.1292/jvms.10-0067
|View full text |Cite
|
Sign up to set email alerts
|

A Serological Survey of Canine Respiratory Coronavirus and Canine Influenza Virus in Korean Dogs

Abstract: ABSTRACT. The relationship between canine respiratory coronavirus (CRCoV) and canine influenza virus (CIV) seropositivity in dogs in Korea was examined. Sixty-two of the 483 samples (12.8%) were seropositive for CRCoV by indirect fluorescent antibody (IFA) analysis. Nineteen animals were seropositive for CIV by ELISA out of the 385 samples tested. Serum antibodies for both viruses were detected in 6 of the 483 dogs sampled, suggesting that these viruses are present in dogs in Korea. Although the role of CRCoV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
26
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 16 publications
2
26
1
Order By: Relevance
“…A recent study in South Korea reported CIRD in dogs caused by CIV (H3N2) and CRCoV [1,2]. Interestingly, in this study, we indentified four dogs co-infected with CIV and CDV and, one dog co-infected with CRCoV and CDV.…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…A recent study in South Korea reported CIRD in dogs caused by CIV (H3N2) and CRCoV [1,2]. Interestingly, in this study, we indentified four dogs co-infected with CIV and CDV and, one dog co-infected with CRCoV and CDV.…”
mentioning
confidence: 52%
“…CIV H3N2 strain is associated with the development of acute respiratory disease in dogs, and is a novel pathogen for CIRD in South Korea and South China [18,25]. Serological surveys carried out in South Korea, Italy, U.K., Ireland, U.S.A. and Japan [2,6,7,22,24], have identified CRCoV as a worldwide pathogen found in the respiratory tract of dogs suffering from mild or severe respiratory disease. CDV is one of the most serious diseases in domestic dogs worldwide [11,13,14,16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…20 Additional serologic testing on companion animals not linked to dog farms or kennels showed H3N2 antibody prevalence rates of less than 5%. 21,22 Even though the prevalence is at a low level, the data do indicate that an H3N2 influenza virus is infecting dogs in South Korea. At this time there are no reports of H3N2 infections in other parts of the world.…”
Section: H3n2mentioning
confidence: 98%
“…All serum samples were treated with a receptor-destroying enzyme and absorbed with erythrocytes to remove nonspecific inhibitors before the assays. All samples were tested by Hemagglutination Inhibition (HI) and Neutralization (NT) assays according to the manufacturer's instructions as previously reported [1,3,6,10]. HI titer≥40 and NT titer≥40 are considered seropositve and indicate previous infection.…”
mentioning
confidence: 99%